A Study of the Perceptions of Professional-Year Students of the 76th Cohort Regarding the Integrated Surgical Clerkship Program at the Faculty of Medicine, Jenderal Achmad Yani University - Fitriardi Sejati; Sylvia Mustika Sari; Tamma Rahagi Wibowo; Pramesthi Kusumawardani; Shabrina Nuur Afifah (Green Publisher Indonesia, 2026)
The transition of medical professional students from the preclinical stage to the clinical stage is a period filled with critical academic and psychological challenges. The concept of an integrated clerkship is needed to support experiential learning, improve self-confidence, and minimize the risk of medical errors due to system unpreparedness. Evaluation of the Integrated Surgical Clerkship (ISC) program at the Faculty of Medicine, Jenderal Achmad Yani University (FK Unjani) is an essential step to ensure effective curriculum implementation.This study aimed to describe the perceptions of professional-year students of the LXXVI cohort regarding the effectiveness and implementation of the ISC program at the Faculty of Medicine, Unjani. A descriptive quantitative study with a cross-sectional design was conducted on all professional-year students of Cohort LXXVI (N = 120) using a total sampling technique. Data were collected using a validated questionnaire consisting of 26 items. Data analysis was performed using descriptive statistics. The instrument demonstrated very high reliability, with a Cronbach’s alpha of 0.982. The respondents consisted of 83 female students (69.2%) and 37 male students (30.8%). Students’ perceptions of the ISC program were in the very good category, particularly in the domains of clinical readiness and mentor quality. The ISC program was found to be effective in supporting the transition to clinical education and is recommended for continued implementation.